Road infrastructure and climate change in Vietnam - Paul S. Chinowsky; Amy E. Schweikert; Niko L. Strzepek; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Climate change is a potential threat to Vietnam's development as current and future infrastructure will be vulnerable to climate change impacts. This paper focuses on the physical asset of road infrastructure in Vietnam by evaluating the potential impact of changes from stressors, including: sea level rise, precipitation, temperature and flooding. Across 56 climate scenarios, the mean additional cost of maintaining the same road network through 2050 amount to US10.5 billion. The potential scale of these impacts establishes climate change adaptation as an important component of planning and policy in the current and near future.
Keywords: Q18; R42; 330; climate change; road infrastructure; stressor response functions; Vietnam; Klimawandel; Straße; Vietnam